Subjective well being in Argentina in the 2005-2007 period. Happiness determinants in accordance with the Survey of Argentina’s Social Debt (Encuesta de la Deuda Social Argentina-EDSA) (Revista de Psicología, 2019)
This paper has as main objective to study the determinants of the self-perception of happiness in Argentina between the years 2005 and 2007, by using information gathered from the Survey of Argentina’s Social Debt (Encuesta de la Deuda Social Argentina-EDSA) carried out by the Catholic University of Argentina (Universidad Católica Argentina-UCA). The study was performed by means of a statistical-descriptive analysis and a series of multivariate econometric models of the arranged logit type that allowed to identify the perception of enough determinants having an effect on the self-perception of happiness in a positive and statistically significant way: the income; the self-perceived health status; the employment and its quality; the civil status; the quantity of children in the home; the least perceived discrimination; the communion with God; and the free time.
Keywords: Behavioral Economics; Social Perception; Employee Skills; Marital Status; Family Size; Religious Biliefs